IMPROVING STUDENT LEARNING OUTCOMES IN GRADE VI THROUGH THE INFLUENCE OF EMOTIONAL INTELLIGENCE AT MADRASAH IBTIDAIYAH NEGERI PARANNAPA JAE, PADANG LAWAS REGENCY, INDONESIA - Syafnan Syafnan; Fitriani Surayya Lubis; Laila Surayya; Arief Rahman (IAIN Padangsidimpuan, 2023)
This research aimed to answer the following questions: (1) What is the level of emotional intelligence of grade VI students at MIN Parannapa Jae? (2) What are the learning outcomes of grade VI students at MIN Parannapa Jae? (3) Is there a significant influence of emotional intelligence on the learning outcomes of grade VI students at MIN Parannapa Jae? The research was conducted using a correlational quantitative approach and ex post facto method. The findings of this study were obtained from the documentation study conducted by the researcher using the students' report cards in grade VI at MIN Parannapa Jae. The highest score obtained was 96, while the lowest score was 78. The report card scores were grouped into 5 classes with a class interval of 4. Based on Table 4.4, the mean score was 84.46, the median was 85, the mode was 80, and the standard deviation and variance were 5.753 and 33.103, respectively.